Plasmids coding for colonization factor antigen I and heat-stable enterotoxin production isolated from enterotoxigenic Escherichia coli: comparison of their properties. - McConnell, M M (1981)
We examined seven enterotoxigenic Escherichia coli strains which produced colonization factor antigen I (CFA/I). Four of these strains were from South Africa (three serotype O78:H12 and one serotype O63:H-), one was from Ethiopia (O78:H12), and two were from Bangladesh (O78:H11 and O78:H12). Plasmids coding for CFA/I were mobilized from six of these strains by using resistance or enterotoxin factors. No plasmid was mobilized from the serotype O78:H12 Bangladesh strain. The transconjugants obtained from crosses with the O78 strains also produced heat-stable enterotoxin (ST), and additional investigations showed that CFA/I and ST were coded for by a single non-autotransferring plasmid. These plasmids were fertility inhibition negative, did not restrict any of the coliphages with which they were tested, and were incompatible with each other. Four had molecular weights of approximately 60 X 10(6), and one had a molecular weight of 52 X 10(6). Like the other CFA/I plasmids, the CFA/I plasmid transferred from the O63:H- strain coded for ST, but this plasmid also coded for heat-labile enterotoxin. In most other respects the properties of this plasmid were similar to those of the CFA/I-ST plasmids previously described. The molecular weight of this plasmid was 65 X 10(6). The IncT R-factor Rtsl was marked with a transposon for tetracycline resistance and then transferred into the two Bangladesh wild-type strains. Plasmids which coded for tetracycline resistance, CFA/I, and ST were transferred from these strains. These plasmids were incompatible with Rtsl and with the CFA/I-ST plasmids described above and were recombinants between Rtsl and a CFA/I-ST plasmid. Their properties are also described.